Hadith Criticism in Islam: Basic Concepts, Definitions, and Historical Development - Abid Nurhuda; Aurizan Himmi Azhar; Nur Muhammad Lathif (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Hadith occupies a central position in the normative structure of Islam as the second source of law after the Qur’an and the historical medium for transmitting the teachings of the Prophet Muhammad (peace be upon him). However, the humanistic nature of hadith narration makes the problem of authenticity an unavoidable epistemological issue. This article aims to analyze hadith criticism in Islam as a historical and scientific process that develops from personal belief to systematic methodological standards. This research uses a library study method with a historical-epistemological approach to classical and contemporary literature on hadith science. The results of the study indicate that hadith criticism has been present since the time of the Prophet Muhammad (peace be upon him) through direct verification mechanisms, developed during the era of the Companions and Tabi’in through the affirmation of the importance of sanad (chain of transmission), and reached methodological maturity in the codification and post-codification periods through the disciplines of rijāl, jarḥ wa ta’dīl, and musthalaḥ al-ḥadīth. In the medieval period, hadith criticism functioned as a means of preserving and perfecting the scientific heritage through the traditions of shari’ah and takhrij. Meanwhile, in the modern era, hadith criticism has been adaptive and dialogical in responding to the challenges of Orientalism and the Qur’anic scripturalism movement. This article asserts that hadith criticism is not a rejection of the Sunnah, but rather a foundation of scientific rationality that safeguards the Prophet’s authority from historical distortion and ensures its relevance throughout the ages.